Severe COVID-19 in Third Trimester Pregnancy: Multidisciplinary Approach. (16th October 2020) - Pelayo, Jerald; Pugliese, Gabriella; Salacup, Grace; Quintero, Eduardo; Khalifeh, Adeeb; Jaspan, David; Sharma, Bhavna
Abstract : The rapidly expanding cases of the coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have exposed vulnerable populations, including pregnant women to an unprecedented public health crisis. Recent data show that pregnancy in COVID-19 patients is associated with increased hospitalization, admission of the intensive care unit, and intubation. However, very few resources exist to guide the multidisciplinary team in managing critically ill pregnant women with COVID-19. We report our experience with managing a morbidly obese pregnant woman at 36 weeks' gestation with history of asthma and malignancy who presented with persistent respiratory symptoms at an outside hospital after being tested positive for SARS-CoV-2 polymerase chain reaction (PCR). Early in the course of the hospitalization, patient received remdesivir, convalescent plasma, bronchodilator, systemic steroids, and IV heparin for COVID-19 and concomitant asthma exacerbation and pulmonary embolism. Due to increasing oxygen requirements, she was eventually intubated and transferred to our institution for higher level of care. Respiratory acidosis, severe hypoxemia, and vent asynchrony were managed with vent setting adjustment and paralytics. After 12 hours from spontaneous rupture of her membranes and with stabilization of maternal status, patient underwent a term cesarean delivery for nonreassuring fetal heart tracing. The neonate was discharged on the 2 nd day of life, while the patient was extubated on the 6 th postpartum day and was discharged to acute inpatient rehabilitation facility on the 19 th hospital day. This report highlights the disease progression of COVID-19 in a pregnant woman, the clinical challenges in the critical care aspect of patient management, and the proposed multidisciplinary strategies utilizing an algorithmic approach to optimize maternal and neonatal outcomes.